Colorless polyimides derived from norbornyl bis-benzocyclobutene-containing diamines. Issue 1 (28th November 2022) - Miao, Jie; Zhang, Mengru; Pang, Yuanyuan; Zheng, Zejun; Tian, Chun; Wang, Zhen; Yan, Jingling
Abstract : Colorless polyimides with high glass transition temperatures and excellent optical transparency were developed from norbornyl bis-benzocyclobutene-containing diamines, and the structure–property relationship of these polyimides was established. Abstract : Two diamines containing norbornyl bis-benzocyclobutene (N2BC) units (CANAL-2 and CANAL-4) were synthesized by catalytic norbornene–arene annulation reactions between bromoanilines and norbornadiene, and the regioisomers of CANAL-4 were separated using column chromatography. Two sets of colorless polyimides (CPIs) were then prepared via a traditional one-step method using CANAL diamines and commercial dianhydrides as the monomers. The N2BC-containing CPIs displayed exceptionally high glass transition temperatures ( T g ) of 418–480 °C, good optical properties (61–84% transmittance at 400 nm), and modest coefficients of thermal expansion (CTE) as low as 23.9 ppm K −1 . For the given dianhydrides, the CPIs from CANAL-4 demonstrated similar lower interchain distances, lower T g, lower CTE, and better mechanical properties compared to the CANAL-2-derived ones. These differences can be explained by the reduced rotational barrier but more pronounced inter- and intra-molecular interactions originating from their less ortho -methyl substituents. The CPIs from anti -CANAL-4 exhibited more compact chain packing and thus better dimensional stability as compared to those from syn -CANAL-4. For certain diamines, the CPIs from norbornane-2-spiro-α-cyclopentanone-α′-spiro-2′′-norbornane-5, 5′′, 6, 6′′-tetracarboxylic dianhydride (CpODA) showed the best integrated properties due to the rigid and contorted CpODA residues, and additional dipole–dipole interactions of the ketone moieties. These CPIs show great promise as candidate materials for optical and optoelectronic applications because of their excellent combination of light coloration, and balanced thermal and mechanical properties.